(untitled) (De Musica, 2024)
The article presents an analysis of the complex relationship between music and language by comparing two contrasting semantic approaches. The aim is twofold: 1) to highlight the implications of different theories of meaning for the understanding of music; 2) to determine which approach is better suited to the theoretical challenges raised by this comparison. The perspectives considered appear to be mutually incompatible, each emphasising different facets of the musical phenomenon. On the one hand, the referentialist perspective treats music like natural-historical languages with their denotative capacities, emphasising the undeniable fact that music prompts interpretation, conveys content and carries meaning. Semiotic analysis, on the other hand, presents music as structured acoustic material whose only content is the representation of formal relations. The coexistence of the two perspectives is possible if the focus of comparison is shifted from the products of linguistic and musical activity to the operating principle of the two phenomena. The common operating principle is found in the general capacity for sign articulation outlined by Saussure in the Course in General Linguistics. Once this perspective is adopted, it becomes possible to reconcile the content-oriented instances of musical interpretation with its formal description.